Integrating Climate Education for Social Welfare Enhancement in Indonesia - Nugroho, Leonta Anggun; Raafi, Muhammad (PT Keberlanjutan Strategis Indonesia, 2026)
Indonesia still faces two significant challenges: a climate education system and relatively low social welfare rates. To address these pressing concerns, this study examines the feasibility of utilizing climate education to enhance social welfare. The study proposes a comprehensive framework for climate education in Indonesia using quantitative and qualitative research methods designed to adapt to various contexts, including formal educational settings such as schools and universities, while still accessible to underprivileged communities. The findings highlight the significance of integrating climate and environmental education into the educational system to prepare future generations to address ecological challenges. The paper also discusses the impact of the climate crisis on social welfare conditions in Indonesia, particularly for vulnerable communities. It proposes strategies for implementing climate education to enhance social welfare. It emphasizes the need for interactive and action-oriented approaches to climate education, as well as the role of universities in promoting practical solutions and student leadership. The framework presented in the paper aims to equip future professionals with the necessary tools and knowledge to drive innovation in sustainable technologies, shape responsible policy decisions, and foster community resilience.